2001
DOI: 10.1002/jmri.1156
|View full text |Cite
|
Sign up to set email alerts
|

Autocorrelation analysis of bone structure

Abstract: We propose a method called spatial autocorrelation analysis (SACA) to determine the spatial anisotropy of the trabecular bone in order to investigate osteoporosis. For demonstrating the potential of SACA we first evaluate the method on rectangular, simulated test patterns as a simple model for the anisotropic pore structure of the bone. As a next step towards biomedical application, photographic reference images of human vertebral bone were investigated by SACA. Osteoporotic bone structure could be clearly dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 11 publications
0
20
0
Order By: Relevance
“…SMI proved to be useful for characterizing structures derived from TB m-CT images of human specimens from multiple anatomic locations and providing insight into age-related changes in TB architecture (13). Other 3D approaches make use of the quasi-regularity of trabecular networks (125,126). Hwang et al (125) showed on the basis of micro-MRI data obtained in specimens of human trabecular bone that spatial autocorrelation analysis, discussed later in more detail, can provide information on intertrabecular spacing and orientation without the need to resort to binary images.…”
Section: D Structure Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…SMI proved to be useful for characterizing structures derived from TB m-CT images of human specimens from multiple anatomic locations and providing insight into age-related changes in TB architecture (13). Other 3D approaches make use of the quasi-regularity of trabecular networks (125,126). Hwang et al (125) showed on the basis of micro-MRI data obtained in specimens of human trabecular bone that spatial autocorrelation analysis, discussed later in more detail, can provide information on intertrabecular spacing and orientation without the need to resort to binary images.…”
Section: D Structure Analysismentioning
confidence: 99%
“…For such a lattice, the first peak of the autocorrelation function (ACF) occurs at the lattice spacing whereas the full width at half maximum of the parent peak is a measure of structural thickness. Rotter et al (126) proposed AC analysis as a means of characterizing TB. More recently, Wald et al worked out an algorithm for mapping the full anisotropy ellipsoid for TB thickness and spacing from in vivo MR images (153).…”
Section: D Structure Analysismentioning
confidence: 99%
“…Recent studies determined the anisotropy from high resolution magnetic resonance datasets using autocorrelation analysis on clinically gained datasets. These experiments were restricted to peripheral sites (Rotter et al, 2001;Wald et al, 2007). Rao and Schunk (1991) proposed the gradient structure tensor (Y GST ) to determine texture orientation.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of connecting rods perpendicular to the major loading axis in the context of femoral bone strength has been previously emphasized [242]. More recent approaches include topology-based orientation analysis of trabecular bone networks [233] and 3D spatial autocorrelation function (ACF) [243,244]. ACF is defined as the convolution of the image with its complex conjugated mirrored image.…”
Section: High-resolution Imaging Techniques For Bone Quality Assessmentmentioning
confidence: 99%